Business Model Innovation for Small Medium Enterprises - Swasty, Wirania (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
Indonesian economy through Small Medium Enterprises (SMEs) is expected to absorb labor and contribute to the growth of Gross Domestic Product. However, SMEs lack both managerial and technical skills. This research is about business model innovation for SMEs especially in fashion and garment industry. Study used qualitative approach by mentoring four selected SMEs in Babakan Penghulu Village– Cinambo Sub-District, Eastern Bandung. The tools used to analyze them including PEST analysis, Porter’s Five Forces,Resource Based View, Value Chain Analysis and Business Model Canvas. Finding suggests SMEs to have business model innovation derived from value proposition. SMEs should build their own brand awareness. Moreover, as garment and fashion industry, design can be a particularly important part of the Value Proposition. SMEs could communicate its value propositions and inform their service through its official websites and other social media. Since the intangible resources include brand and design, thus SMEs should build brand image and innovate year by year. SMEs must hire designers and launch a series of new products offers under the signature of their own brands. Ideation to strengthen strategies derives from value proposition building block as a starting point. Moreover, Business Model Canvas makes strategy more focused and measurable. Business model innovation is expected to increase overall performance of SMEs.